J02 Physical therapy for patients with Huntington's disease: effects of a treatment program and intercorrelation between outcome measures. (16th November 2010) - Ekwall, C; Bohlen, S; Reilmann, R; Wiklund, L
Abstract : Objective: To evaluate the effect of a physiotherapeutic exercise program for patients with HD concerning motor function and disability, balance and fall related self-efficacy, and to investigate the correlation between the seven assessment tools used in the study. Design: Pre-post interventional study with baseline assessments and a quasi experimental within-group design. Setting: Out-patient clinic at a university hospital. Participants: Twelve persons with genetically confirmed Huntington's disease at an early or middle stage of the disease and with a mean age of 52, 7 SD (16, 4). Methods: The intervention comprised physiotherapy aimed to improve motor function, disability, balance, and fall-related self-efficacy, and there was a treatment focus on improvement of transitions, walking, balance, posture, postural control and fall-related self efficacy. Baseline assessments including five clinical tests and two questionnaires were made 6 weeks and 0 weeks prior to the intervention. The same tests were used 0 and 6 weeks after the intervention. Outcome measures: Over all motor function and disability measured with the Unified Huntington's Disease Rating Scale; Total Motor Score and Total Functional Assessment, static and dynamic balance measured with the One-leg stance-test, the Timed Up and GO Test, the Figure of eight-test and the Berg Balance Scale and fall-related self-efficacy measured with the Falls Efficacy Scale. Results: The physiotherapeutic exercise program demonstrated a significant improvement in balance measured with Berg balance scale ( p=0.045) and indicated some positive effects on the participant's motor function ( p=0.076 ) and fall-related self efficacy ( P=0.089 ). The significant correlation coefficients between the different measurements of motor function, disability, balance and fall related self-efficacy range from 0.68 to 0.87. Conclusions: Physical therapy focused on transitions, walking, balance, posture, postural control and fall-related self efficacy twice a week for 6 weeks at an out-patient setting had a positive effect on the participants' motor performance. Berg's balance scale appeared to be a useful instrument for patients with HD.